2022
DOI: 10.1089/can.2020.0048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Potency Cannabis on Psychomotor Performance in Frequent Cannabis Users

Abstract: Background: Recently increased access to cannabis products in the United States has been associated with increased rates of driving after cannabis use. Although numerous studies indicate that cannabis impairs psychomotor and neurocognitive functions that can affect driving ability, the determination of cannabis-impaired driving risk is complicated by the extent to which frequent cannabis users develop tolerance to THC's subjective, cognitive, and psychomotor effects, and by the fact that there is no validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
(41 reference statements)
3
13
0
Order By: Relevance
“…age, genetics, body fat percentage, and user experience level with cannabis) may impact the pharmacodynamics of cannabis. Fourth, while the DRUID ® showed promise in this initial study as well as in another recent study (Karoly et al, 2020) in terms of its sensitivity to cannabis effects, more research is needed on this novel instrument. Lastly, though the sample size (N = 20) in this study was sufficient to achieve the study aims, replication in larger and more diverse samples is encouraged.…”
Section: Discussionmentioning
confidence: 87%
“…age, genetics, body fat percentage, and user experience level with cannabis) may impact the pharmacodynamics of cannabis. Fourth, while the DRUID ® showed promise in this initial study as well as in another recent study (Karoly et al, 2020) in terms of its sensitivity to cannabis effects, more research is needed on this novel instrument. Lastly, though the sample size (N = 20) in this study was sufficient to achieve the study aims, replication in larger and more diverse samples is encouraged.…”
Section: Discussionmentioning
confidence: 87%
“…However, we acknowledge that not all studies support this position [10,[32][33][34]. Experimental and driving simulator studies have shown that marijuana affects motor skills and executive function [35][36][37][38][39], but this need not correspond to increased crash risk. For instance, Lacey et al found no evidence of an association between THC presence in drivers and the odds of fatal crash involvement [40].…”
Section: Discussionmentioning
confidence: 91%
“…The Druid ® mobile application is administered via tablet to assess cognitive and psychomotor motor impairment due to any cause or combination of causes including cannabis [ 21 , 38 ], alcohol [ 39 ], illicit drugs, prescription medications, chronic medical conditions, illness, and fatigue. The app has users perform four tasks, presented in quick succession, that measure cognitive-motor performance by assessing balance, decision-making accuracy, reaction time, hand-eye coordination, and time estimation under conditions of divided attention.…”
Section: Methodsmentioning
confidence: 99%